Influencer marketing and purchasing decisions in the fashion sector among young people, Lima Perú 2025 - Barinotto Roncal, Patricia; Cáceres Peréz, Heidy; Reynoso Sicha, Claudia; Palma Vallejo, Juana Graciela (LACCEI, 2025)
This research study aims to determine the relationship between influencer marketing and purchasing decisions in the fashion sector among young people in San Juan de Lurigancho, 2025. The digital strategy of influencer marketing is currently one of the most efficient for companies, since influencers currently generate an emotional and aspirational connection with young people through the content they transmit on social networks. It should be noted that, after the COVID-19 pandemic, this strategy obtained notable growth due to the digitalization of fashion sector businesses, which reinforced the key role of influencers as agents who disseminate recommendations or share experiences about brands. This research has a quantitative approach, applied with a causal correlational scope, a non-experimental and cross-sectional design, with a sample of 206 young people. Furthermore, using a virtual questionnaire administered through Google Forms as a data collection technique, it was found that influencer marketing is significantly related to purchasing decisions, reporting a Sperman Rho coefficient of 0.654 (sig.